2011
DOI: 10.1128/ec.00013-11
|View full text |Cite
|
Sign up to set email alerts
|

SclR, a Basic Helix-Loop-Helix Transcription Factor, Regulates Hyphal Morphology and Promotes Sclerotial Formation in Aspergillus oryzae

Abstract: Most known basic-region helix-loop-helix (bHLH) proteins belong to a superfamily of transcription factors often involved in the control of growth and differentiation. Therefore, inappropriate expression of genes encoding bHLH proteins is frequently associated with developmental dysfunction. In our previously reported study, a novel bHLH protein-encoding gene (AO090011000215) of Aspergillus oryzae was identified. The genedisrupted strain was found to produce dense conidia, but sparse sclerotia, relative to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
57
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 37 publications
4
57
0
Order By: Relevance
“…Our results show that UrdA does not control nsdD expression, suggesting that sexual and asexual developmental pathways are coordinated at different levels ( Figure 9). Jin et al (2011a) indicated that the A. oryzae ortholog of UrdA, EcdR, is required for early asexual development and proposed that it was repressed by its interaction with SclR, an additional HLHtype transcription factor that promotes sclerotial formation (Jin et al 2011b). However, expression of the putative ortholog of sclR, An7170, is not significantly altered when flbB is deleted.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that UrdA does not control nsdD expression, suggesting that sexual and asexual developmental pathways are coordinated at different levels ( Figure 9). Jin et al (2011a) indicated that the A. oryzae ortholog of UrdA, EcdR, is required for early asexual development and proposed that it was repressed by its interaction with SclR, an additional HLHtype transcription factor that promotes sclerotial formation (Jin et al 2011b). However, expression of the putative ortholog of sclR, An7170, is not significantly altered when flbB is deleted.…”
Section: Discussionmentioning
confidence: 99%
“…This might involve the manipulation of culture conditions, given that sclerotial formation is dependent on environmental conditions (14) and given the exacting demands of some aspergilli for sexual reproduction (14,47), and/or the use of genetic manipulation techniques to induce sclerotial formation. At present, only one A. oryzae gene, encoding the bHLH transcription factor SclR (for sclerotium regulator), involved in the production of sclerotia has been identified (14,30,31). Deletion of sclR in certain strains observed to form sclerotia was found to result in sparse sclerotial production, while overexpression of sclR led to Ͼ5-fold production of sclerotia with increased formation of branched aerial hy-phae (31).…”
Section: Discussionmentioning
confidence: 99%
“…At present, only one A. oryzae gene, encoding the bHLH transcription factor SclR (for sclerotium regulator), involved in the production of sclerotia has been identified (14,30,31). Deletion of sclR in certain strains observed to form sclerotia was found to result in sparse sclerotial production, while overexpression of sclR led to Ͼ5-fold production of sclerotia with increased formation of branched aerial hy-phae (31). In related work, deletion of a zinc finger calcineurin response gene, crzA, was found to result in the production of mainly immature sclerotia in A. parasiticus (8), so a homolog might also be required for the maturation of sclerotia in A. oryzae.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between regulatory factors controlling the formation of sclerotia and conidiation is not well understood. SclR, the sclerotial pathway-specific helix-loop-helix transcription factor, was reported to promote sclerotial formation and to regulate hyphal morphology in Aspergillus oryzae (23). Deletion of sclR yields strains with sparse sclerotia but produces dense conidia.…”
mentioning
confidence: 99%